A UASB reactor coupled to a hybrid aerobic MBR as innovative plant configuration to enhance the removal of organic micropollutants. (February 2016) - Alvarino, T.; Suárez, S.; Garrido, M.; Lema, J.M.; Omil, F.
Abstract: An innovative plant configuration based in an UASB reactor coupled to a hybrid aerobic membrane bioreactor designed for sustainable treatment of municipal wastewater at ambient temperatures and low hydraulic retention time was studied in terms of organic micropollutants (OMPs) removal. OMPs removal mechanisms, as well as the potential influence of biomass activity and physical conformation were assessed. Throughout all periods of operation (150 days) high organic matter removals were maintained (>95%) and, regarding OMPs removal, this innovative system has shown to be more efficient than conventional technologies for those OMPs which are prone to be biotransformed under anaerobic conditions. For instance, sulfamethoxazole and trimethoprim have both shown to be biodegradable under anaerobic conditions with similar efficiencies (removal efficiencies above 84%). OMPs main removal mechanism was found to be biotransformation, except in the case of musk fragrances which showed medium sorption onto sludge. OMPs removal was strongly dependent on the efficiency of the primary metabolism (organic matter degradation and nitrification) and the type of biomass. Highlights: OMPs removal mechanisms in a combined anaerobic/aerobic/membrane reactor system. OMPs mass balance (liquid, solid phase) under steady state and fed-batch operation. Quantification of OMPs sorption dynamics in flocculent and granular biomass. Biotransformation of OMPs occurs by co-metabolism. Biotransformation of OMPs dependent on C and N metabolism.